Can HIV‐positive gay men become parents? How men living with HIV and HIV clinicians talk about the possibility of having children. Issue 2 (22nd November 2020) - Pralat, Robert; Burns, Fiona; Anderson, Jane; Barber, Tristan J.
Abstract: It is now established that people living with HIV who have an undetectable viral load and adhere to antiretroviral treatment cannot transmit HIV to their sexual partners. Previous research has shown that 'being undetectable' changes how HIV‐positive gay men experience their sex lives. But how does it affect gay men's reproductive behaviours? And what influence does it have on views about parenthood at a time when gay fatherhood has become more socially accepted and publicly visible? Drawing on qualitative interviews with patients and clinicians at four HIV clinics in London, we identify differences in how interviewees talked about the possibility of having children for HIV‐positive men. Both groups, unprompted, frequently referred to sperm washing as a method enabling safe conception. However, whereas clinicians talked about sperm washing as an historical technique, which is no longer necessary, patients spoke of it as a current tool. The men rarely mentioned being undetectable as relevant to parenthood and, when prompted, some said that they did not fully understand the mechanics of HIV transmission. Our findings offer new insights into how biomedical knowledge is incorporated into people's understandings of living with HIV, raising important questions about how the meanings of being undetectable are communicated.